PENERAPAN MODEL KOOPERATIF LEARNING TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Apip Abdul Roup (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
This study aims to improve student learning outcomes class VIII-A MTs Negeri 4 Garut in Mathematics subject matter building space. This type of research is a classroom action research conducted in two cycles, each of which is carried out in 2 meetings. Each meeting consists of the planning, action, observation and reflection stages. The subjects in this study were all students of class VIII-A MTs Negeri 4 Garut in the odd semester of the 2019-2020 school year, totaling 29 students. The data obtained in this study include: learning outcomes and student learning completeness taken from giving test questions at the end of each meeting and student activeness in the learning process. From the research data, it was obtained that the average student learning outcomes in cycle I was 81 and cycle II was 96. The average completeness of learning in cycle I was 79% and cycle II was 100%. From these data it is clear that from cycle I to cycle II there is a significant increase. From this research, it is concluded that by using the cooperative learning model, learning together can improve the learning outcomes of class VIII-A students of MTs Negeri 4 Garut in Mathematics Subjects in building materials.